Growth, development, and reassessment of hypothyroid infants diagnosed by screening. Issue 6327 (15th May 1982) - Hulse, J A; Grant, D B; Jackson, D; Clayton, B E
Abstract : Thirty]six neonates in whom hypothyroidism was diagnosed after thyroid stimulating hormone screening were reassessed at 1 year. All had grown satisfactorily and the mental development scores were normal in all except two. Treatment was withdrawn in 32 and persistent hypothyroidism was confirmed in 31 cases. Thyroid stimulating hormone concentrations were raised in one-third of cases before the withdrawal of treatment and this was associated with generally lower concentrations of serum thyroxine (T4) and smaller doses of L-thyroxine than in those cases with normal concentrations of thyroid stimulating hormone. In treating congenital hypothyroidism, serum T4 concentrations should be monitored regularly and the dose of thyroxine adjusted to maintain serum T4 in the upper part of the reference range.